Trends in training in the field of computing - Analysis of master’s programs in Colombia (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2015)
This paper presents an analysis of master’s programs that currently exist in Colombiato provide education in the field of computing. For performing this work, a four stepsmethodology was used: i) identification of the academic offer, ii) recompilation of information, iii) classification of the programs iv) and generation of reports and analysis ofthe findings. The main results are the characterization of the academic offer of masterprograms in computing, the names of the programs, their granted academic degrees,and the research areas, which were analyzed and classified by taking as reference thecurricula recommendations by the Association for Computing Machinery - ACM. Finally, this study provides elements that enrich the ongoing discussion that occurs in theacademic community in the country, on the present and future of computer educationat different levels, and particularly in the master level.
Keywords: Computing; Exploratory study; Master programs; Colombia